Co-integration efficiency of three different human DNA fragments in mice - CHU Xiao-hong; ZHENG Xin-min; YANG Gong-she; HU Jin-ping; WENG Jing-qiang (浙江大学学报. 农业与生命科学版, 2004)
In this paper, three different human DNA fragments-human serum albumin gene (HSA), hFEN1 DNA repair gene and an uncoding large DNA fragment CIT 987SK-384D8 were successively injected into the male prenuclei fertilized eggs of mice. Then, the injected eggs were selected and transferred to the oviduct of pseudopregnant recipent mice and gave birth to 65 F1 offsprings. Using PCR and Southern blotting technique the foreign genes were found to have been successfully integrated in 12 of 65 mice. The cointegration efficiency of the DNA fragment of HSA and CIT 987SK-384D8 was 1.298%, and that of hFEN1 0.552%. The total integration rate of microinjection was 3.84% and the overall efficiency was 1.92%. This study indicates that co-injection of non-antagonistic genes is a promising method in production and scientific research of transgenic animals.